Skeletal angiomatosis - rare cause of bone destruction: A case report with review of literature - Malik Reeni; Malik Rajesh; Tandon Suneet; Tandon Puneet (Wolters Kluwer Medknow Publications, 2008)
Classification of skeletal angiomatosis into aggressive and nonaggressive types is on the basis of their clinical behavior and pattern of skeletal involvement (regional and disseminated). Gorham′s disease (massive osteolysis) is an aggressive form of skeletal angiomatosis that shows regional involvement, frequently involving the shoulder and hip areas. Cystic angiomatosis is a nonaggressive form of skeletal angiomatosis with multifocal involvement, predominantly affecting the trunk bones. The imaging modalities gave the diagnosis of cystic angiomatosis of humerus showing multicystic lytic areas. The histopathological differential diagnosis was cystic angiomatosis and Gorham′s disease, as microscopically both are indistinguishable from each other. Both represent a complex network of dilated thin-walled capillaries growing in the marrow space associated with the destruction of bone and infiltration into the adjacent soft tissues. The case is presented because of its extreme rarity and due to the diagnostic dilemma, whether to label it as Gorham′s disease or as cystic angiomatosis. Considering the site involved and its aggressiveness, the diagnosis is in favor of Gorham′s vanishing bone disease as cystic angiomatosis is multicentric and nonaggressive, involving mostly vertebrae and skull with multicystic lytic lesions.